Bulgaria : Report on the Observance of Standards and Codes-Update. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents an update to the Report on the Observance of Standards and Codes for Bulgaria. In 2001-02, Bulgaria continued to use the common General Data Dissemination System (GDDS) as a framework for the further development and improvement in the quality of statistics. In June 2001, the country carried out the first update of the national metadata included in the electronic bulletin maintained by IMF. All existing tables were revised, and three new tables with metadata were developed.